2018
DOI: 10.3390/galaxies6030066
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of Morphological Structures of Planetary Nebulae

Abstract: Abstract:We suggest that most of the mass in planetary nebulae (PNe) resides in the equatorial region and the spherical envelope and the optically bright lobes of PNe are in fact low-density cavities cleared out by fast outflows and photoionized by UV photons leaked from the torus. The nature of multi-polar PNe is discussed under this framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…This process has been observed in PPNe, with examples ranging from the discovery of the butterfly-shaped PPN IRAS 17106-3046 that shows a disk and a bipolar outflow [28], and Hen 2-90 with bipolar morphology and indication of a disk-jet operation [29], to recent detailed observations of the PPN IRAS 16342-3814 that allowed constraints to be out on the mass accretion rate and the accretion channel [30]. Many more examples can be found in reference [31]. Numerical simulations have shown that jets from a companion can interact with the wind of the AGB to form a bipolar PN [32], or a multi-polar PN [33], and more modern simulations have even demonstrated the formation of a 'messy' PN lacking any type of symmetry, also known as a highly irregular PN, and other simulations have emphasized the large variety of morphological features that can be formed by jets [34,35].…”
Section: Ges In Very Massive Starsmentioning
confidence: 90%
“…This process has been observed in PPNe, with examples ranging from the discovery of the butterfly-shaped PPN IRAS 17106-3046 that shows a disk and a bipolar outflow [28], and Hen 2-90 with bipolar morphology and indication of a disk-jet operation [29], to recent detailed observations of the PPN IRAS 16342-3814 that allowed constraints to be out on the mass accretion rate and the accretion channel [30]. Many more examples can be found in reference [31]. Numerical simulations have shown that jets from a companion can interact with the wind of the AGB to form a bipolar PN [32], or a multi-polar PN [33], and more modern simulations have even demonstrated the formation of a 'messy' PN lacking any type of symmetry, also known as a highly irregular PN, and other simulations have emphasized the large variety of morphological features that can be formed by jets [34,35].…”
Section: Ges In Very Massive Starsmentioning
confidence: 90%
“…This process is observed in PPNe, with examples range from the discovery of the butterfly-shaped PPN IRAS 17106-3046 that shows a disk and a bipolar outflow [25], and Hen 2-90 with bipolar morphology and indication of a disk-jet operation [36], to recent detailed observations of the PPN IRAS 16342-3814 that allow putting constraints on the mass accretion rate and the accretion channel [37]. Many more examples can be found in [24]. Numerical simulations showed that jets from a companion can interact with the wind of the AGB to form a bipolar PN [14], or a multi-polar PN [8], and more modern simulations even demonstrated the formation of a 'messy' PN lacking any type of symmetry, a.k.a.…”
Section: Ges In Very Massive Starsmentioning
confidence: 99%
“…Given that PNe reveal a vast diversity in terms of size, shapes, kinematics etc. [16] while the time delay between the WD formation and the final SN Ia explosion can be from almost zero up to several Gyr [17], the parameter space involved in our modeling is immense. Here, as a first attempt, we consider the case of a bipolar PN as this morphology is one the most common PN morphologies.…”
Section: Hydrodynamic Modeling Of the Csm Shaped By Planetary Nebulaementioning
confidence: 99%